Distributive Justice in the Qur'an: A Thematic Analysis of Wealth Verses and Their Implications for Contemporary Islamic Economic Law - Muhayati, Muhammad Zulfi Hamdi; Ashari, Muhammad Pais; Fitri, Amiril Ahmad (Al-'Adl, 2026)
Persistent wealth inequality in modern economic systems has renewed scholarly interest in alternative distributive frameworks. This study examines the Qur'anic concept of wealth distribution and its relevance to the formulation of Islamic economic law, using maqāṣid al-sharī'ah as an interpretive lens. Employing a qualitative-normative approach and the thematic (mawḍū'ī) method of tafsīr, it analyzes selected verses through classical and contemporary commentaries (al-Marāghī, al-Manār, al-Qurṭubī, al-Munīr) read alongside contemporary Islamic economic scholarship. The findings show that the Qur'an establishes an integrated distributive framework — zakat, infāq, ṣadaqah, waqf, and the prohibition of ribā — functioning simultaneously as spiritual obligation and socio-legal instrument against wealth concentration. A comparative legal analysis further shows that although these principles are partially codified in Indonesian legislation (Law No. 23/2011 on Zakat Management; Law No. 21/2008 on Islamic Banking), institutional and regulatory gaps continue to constrain effective implementation, particularly regarding enforcement mechanisms and the continued coexistence of conventional and sharia-compliant finance. The study's contribution lies in systematically connecting Qur'anic distributive ethics to positive law through explicit legal-textual analysis rather than descriptive juxtaposition. The analysis is confined to normative-doctrinal methods and does not assess institutional effectiveness empirically; future socio-legal and empirical research is recommended.